Understanding the diversity of Community Supported Agriculture: a transdisciplinary framework with empirical evidence from Germany - Middendorf, Matthias; Rommel, Marius (Frontiers in Sustainable Food Systems, 2024)
Introduction Community Supported Agriculture (CSA) is an emerging model within alternative food networks (AFNs). It shapes close relationships between food producers and consumers, thereby contributing to food sovereignty and agri-food system transformations. Despite rapid growth from about 10 to over 500 CSAs in just over a decade, the model in Germany still remains niche. We argue that further and faster scaling up requires better understanding of its diversity, yet a comprehensive conceptualization of CSA types is lacking, with insufficient differentiation in research and practice. Methods This study employs a transdisciplinary mixed-methods approach (literature, qualitative, and quantitative data) in cooperation with the German CSA Network. By integrating organizational perspectives, we found that CSAs are highly complex and diverse organizations. Therefore, we firstly aimed at identifying characteristics that we summarized in a CSA framework. In a second stage, we used this framework as guiding structure for co-developing a survey with the Network covering 70 participating CSAs. Results As the defining characteristic within the CSA framework, community financing (domain A) clarifies the uniqueness of the CSA model, thus enables delimitation from other AFN forms. Then differentiation characteristics (domain B) encompass the diversity of CSA configurations. CSA governance (domain B1), regarding the predominant characteristic of organizational governance, distinguish between Producer-led, Consumer-led, and Integrated (all-in-one) CSA types. Varying characteristics (domain B2) specify CSA configurations and enable additional distinction between CSAs. Based on the developed CSA framework, the survey results verify the applicability of governance types in particular, while confirming a high level of diversity of differentiating characteristics in general. Discussion This study can be used to reveal existing generalizations about CSAs, providing a starting point for more nuanced and critical views in research and practice. When seen against the background of AFN and food sovereignty discourses in particular, CSA is an alternative production-distribution model, but not every CSA is governed or structured in alternative ways. CSAs can simultaneously contain both more conventional, traditional elements, as well as more alternative elements. Moreover, the framework provides easy-to-access differentiation criteria for matching members with their most suitable CSAs and vice versa. Overall, this study illustrates that CSA cannot be considered as homogeneous AFN type but be rather marked as a diverse field of its own.